Chains - Anderson, Laurie Halse (New York : Scholastic, 2008)
After being sold to a cruel couple in New York City, a slave named Isabel spies for the rebels during the Revolutionary War.s.
Ages 10 up.
Keywords: Slavery -- Fiction; African Americans -- Fiction; Spies -- Fiction; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Juvenile fiction; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction